Data Driven Decision-Making for Complex Production Systems - Zaoli Yang; Yuchen Li; Ibrahim Kucukkoc (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The complexity of production processes is on the rise due to evolving technology and changing lifestyles. This complexity can stem from factors within the production system or be influenced by characteristics or events external to the system. This reprint aims to conduct rigorous research focused on the application of data-driven decision-making algorithms to address diverse challenges within complex production systems.
Keywords: 650; global value chain; inter-country input-output table; the Belt and Road Initiative; Collaborative Opportunity Index; Collaborative Threat Index; asynchronous dynamic policy; energy-efficient data center; Markov decision process; RG-factorization; sensitivity-based optimization